Literature review of current practices of supplier's assessment and valuation of decisions regarding underperforming suppliers. (2018) - Saidy, Clint; Pinna, Claudia; Wilson, Ziamara; Panavas, Liudas; Harik, Ramy; Bayoumi, Abdel-Moez
This article is a literature review that investigates current practices of supplier's delivery assessment and the valuation of management's decisions regarding underperforming suppliers. The development of this article is intended to aid as literary basis for future development of a comprehensive performance index and a cost function model. Derived from current literature, an underperforming supplier faces three potential outcomes: 1) switching the supplier; 2) increasing collaboration; 3) maintaining the status quo. The decision vis-à-vis failing suppliers is based on an analytical hierarchy process (AHP) since the situation at hand is a multi-criteria decision-making situation. This process enables purchasing firms to assess their suppliers and take proactive measures against underachieving suppliers, which in turn also decreases the risk of supply chain disruption.